1997
DOI: 10.1523/jneurosci.17-06-02187.1997
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Frequency Coding and Activity Dependence of Excitability in Cultured Neurons ofDrosophilaMemory Mutants

Abstract: Mutants of the Drosophila dunce (dnc) and rutabaga (rut) genes, which encode a cAMP-specific phosphodiesterase and a calcium/calmodulin-responsive adenylyl cyclase, respectively, are deficient in short-term memory. Altered synaptic plasticity has been demonstrated at neuromuscular junctions in these mutants, but little is known about how their central neurons are affected. We examined this problem by using the "giant" neuron culture, which offers a unique opportunity to analyze mutational effects on neuronal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
0
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 72 publications
8
85
0
2
Order By: Relevance
“…This is in agreement with the reduction of K + current reported previously for cleavage-arrested giant rutabaga neurons (Zhao and Wu 1997). The reduced current mainly included a non-inactivating component that was sustained throughout the 100 msec.…”
Section: Reduced Ik Dr In Rutabagasupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with the reduction of K + current reported previously for cleavage-arrested giant rutabaga neurons (Zhao and Wu 1997). The reduced current mainly included a non-inactivating component that was sustained throughout the 100 msec.…”
Section: Reduced Ik Dr In Rutabagasupporting
confidence: 92%
“…Moreover, neuronal K + current was shown to be greater in dunce than in wildtype neurons (Alshuaib and Mathew 1998). dunce and rutabaga were shown to display altered firing patterns in giant (cleavage-arrested) cultured neurons (Zhao and Wu 1997). However, neuronal K + current of normal embryonic cultures has not been investigated in the rutabaga mutant.…”
mentioning
confidence: 99%
“…This structural fidelity suggests that pupal M B neurons have an endogenous program directing their morphogenetic development, analogous to that proposed for hippocampal pyramidal neurons (Banker and Cowan, 1979;Dotti et al, 1988). Previous studies of cultured Drosophila neurons of various stages from wild type and mutants allowed morphological and electrophysiological assessment, but without specific identification of the neurons beyond their regional origin (Salvaterra et al, 1987;Byerly and Leung, 1988;Solc and Aldrich, 1988;Wu, 1988;Li and Meinertzhagen, 1995;O'Dowd, 1995;Z hao and Wu, 1997). Primary cultures enriched for M B neurons have been established from brains of other insects (Kreissl and Bicker, 1992;Cayre et al, 1998), but the lack of tools for genetic manipulation limits the versatility of these systems.…”
Section: The Kenyon Cell Culture Systemmentioning
confidence: 80%
“…Mutations in Dunce cause learning and memory defects, which result from altered cAMP hydrolysis and associated elevated cAMP concentrations. 98 It has also been shown that Dunce mutants have altered axonal growth cone motility, 99 neuronal function 100,101 and synaptic plasticity. 102 The PDE4 inhibitors MEM1018 and MEM1091 influence NMDA receptor-dependent memory, 103 and other selective PDE4 inhibitors including rolipram have been shown to influence memory and cognition in several studies.…”
Section: Pde4b As a Risk Factor For Psychiatric Illness: Interaction mentioning
confidence: 99%